Профессиональный французский театр мсье Шово в Камьеше в 1854-1855 гг. - Гуменюк, Р.В; Кокорина, Е.Г. (Культура народов Причерноморья, 2013)
В статье рассматривается одно из проявлений французской военной культуры под Севастополем в период Крымской войны. Стремление солдат организовать досуг и наладить светскую жизнь стало причиной возникновения в лагерях нескольких театров. Целью данной работы является обзор деятельности профессионального французского театра в Камьеше в 1854-1855 гг. Опыт мсье Шово и ряд других причин обусловили значительный успех этого театрального предприятия не только у французов и их союзников, но даже у русских. У статті розглядається один з проявів французької військової культури під Севастополем у період Кримської війни. Прагнення солдат організувати дозвілля та налагодити світське життя призвело до появи в таборах декількох театрів. Метою роботи, що пропонується, є огляд діяльності професіонального французького театру в Кам'єше в 1854-1855 рр. Досвід мсьє Шово та низка інших чинників зумовили значний успіх цього театрального закладу не тільки у французів та їх союзників, та навіть у противників. The article is devoted to the peculiarities of the French military culture near Sevastopol during the Crimean War. Soldiers’ longing for the organized leisure and high life caused the emergence of several theatres in military camps. It is imprinted in many records in the memoirs and letters of the war veterans. The amateur zouave theatre in Inkerman and the theatre of Monsieur Chauveau in Kamiesch were the most famous. The aim of this work is to review the activity of the professional French theatre in Kamiesch that was established by order of Napoleon III Bonaparte in 1854. The performances were daily (only when hostilities were over two days off appeared), professional actors from France played there. The experience of Monsieur Chauveau and a whole number of other factors determined the success of this theatre enterprise among the representatives of different cultures that met in Crimea: French soldiers, their allies and even Russians.